Workshop Implementasi Kurikulum Merdeka Belajar Guru PAUD Di Kecamatan Bajeng - Rika Kurnia R.; Rusmayadi Rusmayadi; Sitti Nurhidayah Ilyas; Parwoto Parwoto; A. Sri Wahyuni Asti (Universitas Negeri Makassar, 2023)
Community Partnership Program (PKM): The aim of the Merdeka Curriculum workshop is to help create enjoyable education for students and teachers. PKM was carried out in July 2022 with partner teachers from the Early Childhood Education Unit in Bajeng District, Gowa Regency, South Sulawesi Province. The PKM participants consisted of teachers and school principals from the Early Childhood Education Unit in Bajeng District. The PKM used lecture, discussion, Q&A, and evaluation methods. The final condition of the Community Partnership Program activity was that the participants could understand the Merdeka Curriculum, understand how to implement it in learning, understand the learning outcomes and the flow of Merdeka learning objectives, and design learning activities that are suitable for the Merdeka Curriculum. The success of PKM can be seen from the high participation and discipline of the participants during the training activities.